2016
DOI: 10.1093/infdis/jiw163
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of HIV-Specific Memory B-Cell Responses in Elite Controllers Despite Low Viral Burdens

Abstract: Human immunodeficiency virus (HIV)-specific B-cell responses in infected individuals are maintained by active HIV replication. Suppression of viremia by antiretroviral therapy (ART) leads to quantitative and qualitative changes that remain unclear. Accordingly, B-cell responses were investigated in elite controllers (ECs), who maintain undetectable HIV levels without ART, and in individuals whose viremia was suppressed by ART. Despite a higher HIV burden in the ART group, compared with the EC group, frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 51 publications
5
30
1
Order By: Relevance
“…Furthermore, we demonstrated that while both cohorts of HIV-infected individuals had an HIV-specific response that was enriched within their resting memory B cells, frequencies were significantly higher in the elite controllers, despite a lower cellular HIV burden than in the ART group (161). These findings confirm those of a previous study (162), and extend observations that an intact humoral immune capacity may be responsible for a superior HIV-specific B-cell response.…”
Section: Correlates Of a Strong B-cell Response Against Hivmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, we demonstrated that while both cohorts of HIV-infected individuals had an HIV-specific response that was enriched within their resting memory B cells, frequencies were significantly higher in the elite controllers, despite a lower cellular HIV burden than in the ART group (161). These findings confirm those of a previous study (162), and extend observations that an intact humoral immune capacity may be responsible for a superior HIV-specific B-cell response.…”
Section: Correlates Of a Strong B-cell Response Against Hivmentioning
confidence: 94%
“…With regard to the populations of memory B cells that circulate in the peripheral blood of elite controllers, we recently demonstrated that they more closely resemble those of healthy donors than those of HIV-infected individuals whose viremia is suppressed by ART (161). Furthermore, we demonstrated that while both cohorts of HIV-infected individuals had an HIV-specific response that was enriched within their resting memory B cells, frequencies were significantly higher in the elite controllers, despite a lower cellular HIV burden than in the ART group (161).…”
Section: Correlates Of a Strong B-cell Response Against Hivmentioning
confidence: 99%
“…In particular, increased proportions of atypical (CD21 lo ) memory B-cells and loss in conventional, Resting Memory (RM, CD21 + CD27 + ) Bcells are hallmark features of chronic infection by HIV or Simian Immunodeficiency virus (SIV) (8). Among atypical memory Bcells, two subsets have been characterized: Tissue-like memory B-cells (TLM, CD21 lo CD27 lo ) enriched in Envelope-specific Bcells (9,10) and Activated Memory B-cells (AM, CD21 lo CD27 + ). Rapid loss in AM B-cells at the acute phase of infection predicts accelerated progression toward the chronic phase (11).…”
Section: Introductionmentioning
confidence: 99%
“…During chronic infection, TLM B-cells produce poly-reactive IgG, part of them being protective/neutralizing Abs. Functional HIV-specific memory Bcells are associated with efficient viral neutralization in Elite controllers (10,15), and significant recovery of HIV-specific RM B-cells requires initiation of anti-retroviral therapy as soon as the acute phase of infection (16).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that there were additional true HIV infections amongst the inconclusive samples: virus replication is responsible for boosting antibody and levels can decline in elite controllers and patients on prolonged ART. [ 14 ], [ 15 ],[ 16 ] Such patients might have undetectable viral loads and low HIV antibody. However, this is rare and unlikely to account for the large number of weakly positive results we encountered.…”
Section: Discussionmentioning
confidence: 99%